Implementasi Guided Imagery amd Slow Deep Breathing untuk Menurunkan Tekanan Darah pada Ibu Hamil di Desa Bangun Rejo Tahun 2025 - Lisdayanti Simanjuntak; Dina Afriani; Eko Murdianto; Sri Mulati Nendah Agreta; Reja Gusmela Lumbantoruan (Aksi Nyata : Jurnal Pengabdian Sosial dan Kemanusiaan, 2025)
Background: Depression is the most common psychological disorder in the last years of an individual's life. Elderly depression has an impact including shortening life expectancy by worsening physical deterioration in the elderly, hindering the fulfillment of elderly development tasks, reducing the quality of life of the elderly, draining the emotions and finances of the affected person and their families and social support systems. Physiotherapist programs given to the elderly who are depressed include listening to English classical music and murottal. Purpose: For this community service activity, this community service activity aims to socialize the provision of English classical music therapy and murottal to reduce the level of depression in the elderly. : This community service activity uses the method of practical lectures and questions and answers. The lecture method was carried out by delivering material on depression and English music therapy. After that, the practice of listening to English and Murotal classical music, while the question and answer method was carried out by asking participants about the material that had been delivered. Results: The results of this community service activity were obtained that participants were able to understand and apply the material that had been delivered. Conclusion: Based on the community service activities that have been carried out, many of the participants enthusiastically received the entire series of events ranging from material presentations, the practice of listening to English classical music to question and answer interactions.